Alteration of UCP2 and ZO-1 expression in trabecular meshwork of neovascular glaucoma patients - Yang, Jian-Gang; Zhou, Chen-Jing; Li, Xiao-Yan; Sun, Peng-Rui; Li, Shao-Peng; Ren, Bai-Chao (Journal of glaucoma, 2015)
The aim of this study was to investigate the expression of uncoupling protein 2 (UCP2) and zonula occludens-1 (ZO-1) in the trabecular meshwork (TM) of neovascular glaucoma (NVG) patients treated with trabeculectomy. Six eyes with NVG underwent trabeculectomy for therapeutic purposes. The data consisted of patient demographics, presurgical and postsurgical visual acuity, intraocular pressure, gonioscopy, and neovascularization of iris and/or the anterior chamber angle. TM samples were obtained from the NVG eyes that had undergone surgery. Immunofluorescence and confocal laser scanning microscopy were carried out to determine the expression of UCP2 and ZO-1 in the TM cells. The baseline median visual acuity was light perception, and the mean intraocular pressure (standard error) was 52.5 (8.3) mm Hg. All eyes displayed neovascularization of the iris and the anterior chamber angle. The expression of UCP2 was significantly decreased in TM cells of NVG compared with the control (P=0.000), whereas increase in ZO-1 expression was detected in staining cells with NVG in comparison with the control (P=0.000). The necrotic cells in the TM were increased (P=0.000), whereas the viable cells were reduced (P=0.000) in comparison with the control. The decreased UCP2 expression and increased ZO-1 expression suggest that the oxidative stress-induced mitochondrial dysfunction and tight junction formation may play pivotal roles in the progress of NVG.